Molecular and Clinical Investigation of COVID-19: From Pathogenesis and Immune Responses to Novel Diagnosis and Treatment - Kashani, Narjes Riahi; Azadbakht, Javid; Ehteram, Hassan; Kashani, Hamed Haddad; Rajabi-Moghadam, Hassan; Ahmad, Ejaz; Nikzad, Hossein; Hosseini, Elahe Seyed (Frontiers in Molecular Biosciences, 2022)
The coronavirus-related Severe Acute Respiratory Syndrome (SARS-CoV) in 2002/2003, the Middle-East Respiratory Syndrome (MERS-CoV) in 2012/2013, and especially the current 2019/2021 Severe Acute Respiratory Syndrome-2 (SARS-CoV-2) negatively affected the national health systems worldwide. Different SARS-CoV-2 variants including Alpha (B.1.1.7), Beta (B.1.351), Gamma (P.1), Delta (B.1.617.2), and recently the Omicron (B.1.1.529) have been emerged resulting from the high rate of genetic recombination and S1-RBD/S2 mutation/deletion in the spike protein that have impact on the virus activity. Furthermore, genetic variability in certain genes involved in the immune system might have an impact on the level of SARS-CoV-2 recognition and immune response against the virus among different populations. Understanding the molecular mechanism and function of SARS-CoV-2 variants, as well as their different epidemiological outcomes is a key step for effective COVID-19 treatment strategies, including antiviral drug development and vaccine designs, which able to immunize people with genetic variabilities against various strains of SARS-CoV-2. In this review, we center our focus on the recent and up-to-date knowledge on SARS-CoV-2 (Alpha to Omicron) origin and evolution, structure, genetic diversity, route of transmission, pathogenesis, new diagnostic and treatment strategies as well as psychological and economic impact of COVID-19 pandemic on individuals and their life around the world.